Third generation biohydrogen pProduction by Clostridium butyricum and adapted mixed cultures from Scenedesmus obliquus microalga biomass - Ortigueira, Joana (2016)
Scenedesmus obliquus biomass was used as a feedstock for comparing the biological production of hydrogen by two different types of anaerobic cultures: a heat-treated mixed culture from a wastewater treatment plant and Clostridium butyricum DSM 10702. The influence of the incubation temperature and the carbon source composition were evaluated in order to select the best production profile according to the characteristics of the microalgal biomass. C. butyricum showed a clear preference for monomeric sugars and starch, the latter being the major storage compound in microalgae. The highest H2 production reached by this strain from starch was 468 mL/g, whereas the mixed culture incubated at 37 C (LE37) produced 241 mL/g. When the mixed culture was incubated at 58 C (LE58), a significant increase in the H2 production occurred when xylose and xylan were used as carbon and energy source. The highest H2 yield reached by the LE37 culture or in co-culture with C. butyricum was 1.52 and 2.01 mol/mol of glucose equivalents, respectively. However, the ratio H2/CO2 (v/v) of the biogas produced in both cases was always lower than the one produced by the pure strain. In kinetic assays, C. butyricum attained 153.9 mL H2/L h from S. obliquus biomass within the first 24 h of incubation, with a H2 yield of 2.74 mol/mol of glucose equivalents. H2 production was accompanied mainly by acetate and butyrate as coproducts. In summary, C. butyricum demonstrated a clear supremacy for third generation bioH2 production from S. obliquus biomass.